Wheat mitochondrial respiration shifts from the tricarboxylic acid cycle to the GABA shunt under salt stress. Issue 3 (1st March 2019) - Che‐Othman, M. Hafiz; Jacoby, Richard P.; Millar, A. Harvey; Taylor, Nicolas L.
Summary: Mitochondrial respiration and tricarboxylic acid (TCA) cycle activity are required during salt stress in plants to provide ATP and reductants for adaptive processes such as ion exclusion, compatible solute synthesis and reactive oxygen species (ROS) detoxification. However, there is a poor mechanistic understanding of how salinity affects mitochondrial metabolism, particularly respiratory substrate source. To determine the mechanism of respiratory changes under salt stress in wheat leaves, we conducted an integrated analysis of metabolite content, respiratory rate and targeted protein abundance measurements. Also, we investigated the direct effect of salt on mitochondrial enzyme activities. Salt‐treated wheat leaves exhibit higher respiration rate and extensive metabolite changes. The activity of the TCA cycle enzymes pyruvate dehydrogenase complex and the 2‐oxoglutarate dehydrogenase complex were shown to be directly salt‐sensitive. Multiple lines of evidence showed that the γ‐aminobutyric acid (GABA) shunt was activated under salt treatment. During salt exposure, key metabolic enzymes required for the cyclic operation of the TCA cycle are physiochemically inhibited by salt. This inhibition is overcome by increased GABA shunt activity, which provides an alternative carbon source for mitochondria that bypasses salt‐sensitive enzymes, to facilitate the increased respiration of wheat leaves. Abstract : See also the Commentary on this article by Sanders, 225 : 1047–1048 .